Spatial gathering characteristics of drought in the Qinghai-Tibet Plateau - Yuan, Ning; Feng, Yuqing; Liang, Sihai; Wang, Guangjun; Yin, Tao; Yan, Dezhao; Wu, Pan; Kuang, Xingxing; Wan, Li (Frontiers in Environmental Science, 2022)
Drought events in the Qinghai-Tibet Plateau (QTP) have become more severer and frequent due to climate change. Understanding the characteristics and variations of drought is crucial to reduce its eco-environmental and socio-economic impacts. This study used the Standardized Precipitation Evapotranspiration Index (SPEI) to identify drought and assess its interannual changes from 1980 to 2020. Then, the Hurst exponent was used to identify future drought changes, and intensity analysis was used to explore the characteristics of drought intensity. Moreover, Empirical Orthogonal Function (EOF) analysis was performed to examine the main spatial gathering characteristics. The results show that the QTP was becoming wetter in general. Drying places accounted for 27% and were mainly in the southeast and northeast of the QTP, as well as the Qaidam Basin. The trend of wet and dry in the future in most regions would be the same as the present, only 10% of the regions would have the reverse trend. The rate of wet/drought changes was faster in the 1980s and 2000s. The EOF mode1 was characterized by a uniform spatial gathering pattern, the west was more sensitive to the variation of dry and wet, and wetting would continue in most areas in the future. EOF mode2 and mode3 mainly indicated opposite gathering patterns of southwest-northeast and south-north.